PELUANG GARAM DAPUR (NaCI) SEBAGAI ALTERNATIF PENGGANTI KCI SECARA PARSIAL DALAM TEKNOLOGI PRODUKSI TANAMAN SORGHUM - Syaiful Anwar (JURNAL LITBANG, 2006)
The study was conducted with the aim to know the probabilirlt of sodium chloride as a partial substitlttion alternative of patassium chloride on sorghum plants cultivution technique. Two varieties ofsarghum (Sl : local ketan and 52 : introduction UPCA-SI) were subjected to K-Na fertilizers (Pl : 100%oK+0%oNa; P2 = 80%K+20%Na; P3 = 6Ao%K+409zoNa; P4 = 40%K+6A%Na; P5 : 20%K+B0%Na; and P6 = A%oK+100%Na). The teatments w^ere allotted to a campletely randomized design with two factorial pattern and 5 replications. The parameters observed were growth of plants (plant height and leafnumber), chlorophyll content, leaf nitrate reductase activity, dry matter, wet matter yield, and dry matter yield. The data were analyzed by variance analysis and Duncan multiple range test 5o%. Results of theexperiments indicated that: (1) The local ketan sorghum had more plant height, chlorophyll content, dry matter and wet matter yield higher than the introcluction UPCA-SI sorghum; (2) Substitution capacity oJ'KCI by NaCl could be reached on 100%o (0%K+100%Na) with highest yield on P4 (40%oK+60%oNa); and (j) The local ketan sorghum had more responsible to fertilizer K-Na than the other one.Keywords: probabiliry, sodium chloride, potassium choride, sorghum